Diversity and distribution of Sargassum spp on Lombok Island - Mursal Ghazali (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Sargassum is a genus that grows naturally in waters with strong currents and rocky bottoms. This genus has high diversity and distribution, including on Lombok Island. This research aims to analyze the diversity and distribution of sargassum on Lombok Island. Research sampling was carried out in 15 locations spread across 4 districts on Lombok Island. Morphological diversity analysis was carried out using MVSP 3.1 software. Meanwhile, distribution is carried out by sampling the distribution in the waters of Lombok Island. The research results showed that the number of Sargassum species found was 4 species. Each species found from different sampling locations has variations with a similarity percentage of 52.8% to 100%. Sargassum was found in 15 sampling locations with the following details: Sargassum polycystum was found in five locations, Sargassum crassifolium in 5 locations, Sargassum cristaefolium in 7 locations, and Sargassum sp in 3 locations.